Evaluation of Visual Biofeedback Modalities for Running Gait Retraining Using a Low-Cost Motion Capture System - Furtado, Daniel A.; Travençolo, Bruno A. N.; Nascimento, Marcelo Z. do; Pereira, Adriano A. (Anais da Escola Regional de Informática do Triângulo Mineiro (ERI-TM), 2026)
Modifying running biomechanics helps optimize movement and reduce joint stress. This preliminary study evaluated the feasibility of two real-time visual biofeedback methods using a low-cost optical motion capture system. In a crossover design, four participants tested a vertical displacement graph interface and an animation interface for cadence synchronization. The results indicate that the graphical biofeedback obtained greater acceptance and ease of immediate motor adaptation. In contrast, the rhythmic interface required greater cognitive demand, generating frustration. Future work will integrate auditory stimuli and adjustments to the test protocol.